DAMPAK LATAR BELAKANG PENDIDIKAN DOSEN PADA PEMAHAMAN MAHASISWA PENDIDIKAN TEKNIK BANGUNAN 2011 - M. FAISAL AKBAR; ELVI MAILANI (JURNAL HANDAYANI PGSD FIP UNIMED, 2014)
ABSTRACT The purpose of the present study was to determine the level of student understanding on a subject, based on the educational background of a teacher who taught in the classroom. The expected result is that students can understand the level of mastery of the material in the learning process based on area of ​​expertise educators. The method used is the method of unstructured interviews, the research procedure that uses interviews, which is a process to collect information for research purposes by way of question and answer face to face between the interviewer or interviewers with the respondents answering or using a tool called a local interview (interview guide ). Conclusion is obtained, the extension building technical education students in 2011 to better understand when taught by lecturers who graduate educational background of the pure scientist. Keywords: Background Education, Understanding, Competence, Professional